The Multilevel Constitutionalism and the protection of human rights and rights of vulnerable groups in Subnational Constitutions - Andrade, Luís Gustavo Medeiros de (2024)
The paper aims to analyze how Multilevel Constitutionalism, more specifically Subnational Constitutionalism referring to State Constitutions, can be used as one more of the multilevel instruments in the protection of human rights.  In topic 1, is carried out an analysis of the organization of the State within the course of Brazilian National Constitutions, demonstrating that there always has been a struggle between centralizing and descentralizing interests of national power. Despite the gradual formal descentralization of the Brazilian State through a quadripartite federation, the 1988 Constitution maintained the almost secular tradition of power concentrations around the central power. In topic 2, is carried out a study of the Subnational Constitutionalism as a modality of Multilevel Constitutionalism, presenting new perspective for the autonomy of the Member States, through a “bottom-up” perspective (from bottom to top), where the potentialities of the space of autonomy of state Constitutions from the legislation of state fundamental rights. In topic 3, is presented a result of a qualitative research carried out in the Brazilian State Constitutions, demonstranting several devices referring to the protection of human rights and vulnerable groups. Thus, it is concluded that the State Constitutions are one more instrument of Multilevel Constitutionalism in the protection of human rights.